Scrum Framework Implementation for Building an Application of Monitoring and Booking E-Bus Based on QRCode - Faris Abdi El Hakim; Agus Prayudi; Kirana Hanifati; Rossi Arisdiawan; Arna Fariza; Hestiasari Rante (JURNAL TEKNIK INFORMATIKA, 2023)
ABSTRACTThe increasing public interest in using the public transportation will reduce the volume of vehicles operating on the streets. The derivative of the description above is how to make people prefer to use bus transportation instead of using private vehicles in traveling within the city. Currently, there is 192.5 million smartphone’s user, in the other hand, the Indonesia government also supported the public transportation such as electrical bus. In November 2022, at KTT G20 Bali, INKA (Indonesia State-Owned Enterprise) and an academic institution consortium released 30 units of electrical buses. From that problem and opportunity, this research aims to propose an application that provides comprehensive information on public transportation, especially inner-city buses. So that, the user could easily track and book the bus. The proposed application is a real-time web-based application aimed at the public as users. This application is accessed using electronic devices such as cell phones, tablets, laptops, and computers. In this research we also proposed conceptual and scrum method for further implementation. We used the Scrum method to build the proposed application, the roles of the scrum team are one product owner, one scrum master, two development teams (UI/UX and developer), and 2 sprints. Implementing the Scrum method in the development process could help organize and increase team productivity. The result of this research is the prototype of a Monitoring and Booking e-Bus Based on a QR Code. In future research we would like to implement this concept and survey the user experience with PIECES framework to get the user comfort in using the proposed application.